Cancer care disparities among Australian and Aotearoa New Zealand Indigenous peoples. Issue 3 (September 2021) - Davies, Amy; Gurney, Jason; Garvey, Gail; Diaz, Abbey; Segelov, Eva
Abstract : Purpose of review: Persistent and significant inequalities for Indigenous people with cancer around the globe exist, arising from colonial settlement of Indigenous land with profound social, economic and cultural impacts. We summarize recent publications concerning cancer disparities affecting Australian Aboriginal and Torres Strait Islander Peoples and Aotearoa New Zealand Māori Peoples. Recent findings: Cancer-free survival and overall survival statistics testify to the urgent need to 'close the gap'. For Indigenous peoples in Australia and New Zealand, disparity persists along the cancer care pathway, from increased risk factors to lower screening access, health resource utilization and survivorship care. Recent publications highlight multimorbidity as contributing to poor cancer outcomes in Indigenous populations. The implementation of tailored Optimal Care Pathways is described, as is the validation of tailored tools capturing the perspectives of Indigenous persons. Finally, the importance of Indigenous-led research is emphasized. Summary: Cancer-specific outcomes in Indigenous people of Australia and New Zealand remain poor with many widening disparities compared to non-indigenous populations. A growing body of epidemiological, health service and clinical research is documenting both the problems and potential solutions. Further work is needed in both broad health policies and the workforce, in building cultural competence to optimize individual care encounters.